Experiential Function in Selected English Nursery Tales - Desna Uli Matanari; Muhammad Yusuf; Fikry Prastya Syahputra (Talenta Publisher, 2026)
The objectives of this study are: to identify the types of processes found in the Selected English Nursery Tales, to identify the types of participants found in the Selected English Nursery Tales, and to identify the types of circumstances found in the Selected English Nursery Tales. The research method used in this study is descriptive qualitative. The research data consists of 678 clauses from two nursery tales, namely Jack the Giant-Killer and Tom Tit Tot, with 489 clauses in Jack the Giant-Killer and 189 clauses in Tom Tit Tot. The data was analyzed using a content analysis model and counting the types of processes, participants, and circumstances found in the Selected English Nursery Tales. The results of this study found that all types of processes in the experiential function were found in the data except for meteorological processes. Material processes were the most dominant processes found in the Selected English Nursery Tales, with a frequency of 405 occurrences (59.47%). In terms of participant types, there were non-human participants (NHP) and human participants (HP). The most dominant Participant I found in the Selected English Nursery Tales is actor with a frequency of 239 occurrences (51.96%). Meanwhile, the most frequently found Participant II in the Selected English Nursery Tales is goal with a frequency of 248 occurrences (49.21%). All types of circumstances are found in the Selected English Nursery Tales, except for circumstance of contingency and circumstance of role. The most frequently circumstance found in the Selected English Nursery Tales is circumstance of location, which has a frequency of occurrence of 191 times with a percentage of 54.57%.